PEMBENTUKAN RANAH AFEKTIF SISWA DALAM PEMBELAJARAN FIKIH DI MA AL URWATUL WUTSQO BULUREJO DIWEK JOMBANG - Qurrotul Ainiyah; Suharti Puji Lestari (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2021)
Demanding knowledge is not just a transfer of knowledge for the benefit of the world, not just intelligence without thinking about spirituality and morals. So that learning must cover all aspects, from intelligence to moral intelligence for everyday life. The affective domain is very important, where today many people understand religion but have not yet practiced it, because affective values ??and religious values ??have not yet become a reflection of their daily attitudes. This study reveals the formation of students' affective domains in fiqh learning which is integrated with the Ahkam Tafsir at Al Urwatul Wutsqo Bulurejo DIwek Jombang which is manifested in the formation of attitudes and awareness of students to apply Islamic law in daily life.